Efforts to Improve Learning Outcomes Part Football Passing in a Football Game through Method Play in Class X Agritan 6 State Vocational School Integrated Agriculture of Riau Province - Yumaidi, Azmi; Yulianti, Mimi (JOURNAL RESPECS (Research Physical Education and Sports), 2024)
This research aims to determine efforts to improve the learning outcomes of passing the legs in the game of football through playing methods in class. This type of research is classroom action research. In this PTK, the research subjects are the students of the class. The research instrument used was the assessment of inside leg passing performance. Based on the analysis and discussion, it can be concluded from the research results that there is an increase in the results of learning to pass the leg in the game of football through the playing method in class. The classical completion score was 80%, only reaching a percentage score of 46.88%, with the number of students who completed it being 15 students, with an average score achieved by students of only 72.27. Meanwhile, in cycle II, it showed that the student's ability to carry out passing movements of the lower legs in the game of football was better with classical completion of 81.25%, and more than 80% had passed with a KKM score (75) with the number of students who completed it being 26 students with The average score achieved by students was 79.17.